Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1016/j.neuron.2006.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Retinal Activity Mediates Development of Ocular Dominance Columns and Binocular Receptive Fields in V1

Abstract: The mechanisms that give rise to ocular dominance columns (ODCs) during development are controversial. Early experiments indicated a key role for retinal activity in ODC formation. However, later studies showed that in those early experiments, the retinal activity perturbation was initiated after ODCs had already formed. Moreover, recent studies concluded that early eye removals do not impact ODC segregation. Here we blocked spontaneous retinal activity during the very early stages of ODC development. This per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 43 publications
6
93
0
Order By: Relevance
“…In the present study, we investigated the impact of cholinergic input on the oscillatory activity of the visual cortex during the first postnatal week, which is a critical period for the fine-tuning of the geniculocortical connections (Cang et al, 2005;del Rio and Feller, 2006;Huberman et al, 2006). Using in vivo recordings from V1 of neonatal rats paired with short-term and long-term modification of the cholinergic input, we showed that (1) acute pharmacological blockade of the cortical mAChR or increase in the ACh level modulates both spontaneous and retina-triggered V1 spindle bursts, (2) electrical stimulation of the BFn responsible for the cortical cholinergic input elicits V1 spindle bursts, and (3) irreversible immunotoxic lesion of the BFn dramatically diminishes the oscillatory spindle bursts activity of the V1 cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the impact of cholinergic input on the oscillatory activity of the visual cortex during the first postnatal week, which is a critical period for the fine-tuning of the geniculocortical connections (Cang et al, 2005;del Rio and Feller, 2006;Huberman et al, 2006). Using in vivo recordings from V1 of neonatal rats paired with short-term and long-term modification of the cholinergic input, we showed that (1) acute pharmacological blockade of the cortical mAChR or increase in the ACh level modulates both spontaneous and retina-triggered V1 spindle bursts, (2) electrical stimulation of the BFn responsible for the cortical cholinergic input elicits V1 spindle bursts, and (3) irreversible immunotoxic lesion of the BFn dramatically diminishes the oscillatory spindle bursts activity of the V1 cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The visual cortex in mice has several well-defined periods under which various developmental processes take place. The period from birth to postnatal day 14 (P14) is characterized by the development of retinotopy and the creation of binocular responses (4,5) whereas the period of P21-P35 is known as the "critical period" for ocular dominance plasticity where binocularity and binocular matching develop, with its peak at P26 (4,6). Although great progress has been made in elucidating changes in connectivity and function during the postnatal maturation of the mouse visual cortex, the transcriptional programs enabling these developmental events are still unknown.…”
mentioning
confidence: 99%
“…The role of synaptic transmission in the refinement of central synapses seems more complex. Although manipulations of presynaptic activity disrupted the refinement of connections in the visual pathway (15)(16)(17), some of the effects were independent of synaptic transmission (18,19).…”
mentioning
confidence: 99%